Co-Stimulatory Bispecific Antibodies Induce Enhanced T Cell Activation and Tumor Cell Killing in Breast Cancer Models - Warwas, Karsten M.; Meyer, Marten; Gonçalves, Márcia; Moldenhauer, Gerhard; Bulbuc, Nadja; Knabe, Susanne; Luckner-Minden, Claudia; Ziegelmeier, Claudia; Heussel, Claus Peter; Zörnig, Inka; Jäger, Dirk; Momburg, Frank (Frontiers in Immunology, 2021)
Although T cell-recruiting CD3-binding bispecific antibodies (BiMAb) have been proven to be clinically effective for hematologic malignancies, the success of BiMAb targeting solid tumor-associated antigens (TAA) in carcinomas so far remains poor. We reasoned that provision of costimulatory BiMAb in combination with αTAA–αCD3 BiMAb would boost T cell activation and proliferative capacity, and thereby facilitate the targeting of weakly or heterogeneously expressed tumor antigens. Various αTAA–αCD3 and αTAA–αCD28 BiMAb in a tetravalent IgG1-Fc based format have been analyzed, targeting multiple breast cancer antigens including HER2, EGFR, CEA, and EpCAM. Moreover, bifunctional fusion proteins of αTAA–tumor necrosis factor ligand (TNFL) superfamily members including 4-1BBL, OX40L, CD70 and TL1A have been tested. The functional activity of BiMAb was assessed using co-cultures of tumor cell lines and purified T cells in monolayer and tumor spheroid models. Only in the presence of tumor cells, αTAA–αCD3 BiMAb activated T cells and induced cytotoxicity in vitro, indicating a strict dependence on cross-linking. Combination treatment of αTAA–αCD3 BiMAb and costimulatory αTAA–αCD28 or αTAA–TNFL fusion proteins drastically enhanced T cell activation in terms of proliferation, activation marker expression, cytokine secretion and tumor cytotoxicity. Furthermore, BiMAb providing costimulation were shown to reduce the minimally required dose to achieve T cell activation by at least tenfold. Immuno-suppressive effects of TGF- and IL-10 on T cell activation and memory cell formation could be overcome by costimulation. BiMAb-mediated costimulation was further augmented by immune checkpoint-inhibiting antibodies. Effective costimulation could be achieved by targeting a second breast cancer antigen, or by targeting fibroblast activation protein (FAP) expressed on another target cell. In tumor spheroids derived from pleural effusions of breast cancer patients, costimulatory BiMAb were essential for the activation tumor-infiltrating lymphocytes and cytotoxic anti-tumor responses against breast cancer cells. Taken together we showed that costimulation strongly potentiated the tumoricidal activity of T cell-activating BiMAb while preserving the dependence on TAA recognition. This approach could provide for a more localized activation of the immune system with higher efficacy and reduced peripheral toxicities.